Assessment of physical properties of granules with paracetamol and caffeine - Michal Szumilo (Saudi Pharmaceutical Journal, 2017)
Caffeine increases the analgesic properties of acetaminophen and therefore it is reasonable to use both substances together in one drug form in stronger pain. Currently, there are no commercially available pharmaceutical combination products containing acetaminophen and caffeine, which is present as granules. The aim of the study was to obtain twelve different granules with these therapeutic substances and determine the effect of various excipients on the quality of the drug form. All the granules were made by wet granulation. Two types of binders were used: polyethylene glycol 6000 (PEG) and polyvinylpyrrolidone K30 (PVP) as well as different types of fillers. The physical properties of granules were assessed in accordance to the requirements of the European Pharmacopoeia 8th ed. The highest apparent density was found in preparations containing calcium hydrophosphate (0.609 g/mL) and the lowest – containing mannitol (0.353 g/mL) as a filler. The Hausner ratio of most prepared granules ranged from 1.05 to 1.11, while the compressibility index ranged from 4.59 to 10.48%. The evaluation of properties of individual granules helped to indicate formulation with good features, which perhaps will be a good alternative to currently available painkillers with caffeine and acetaminophen.